MEASURES AND MEASURES TAKEN ON STATE CONTROL OF THE SHEPHERD FIELD IN SURKHANDARYA DISTRICT: RESULTS AND PROBLEMS - Kasimov Abdisattor Chorievich (Scholar Express Journals, 2023)
In this article, a number of measures and measures taken during the Soviet period to bring the sheep breeding industry under state control, the activities of the state sheep farms established in the Surkhandarya district of the south of Uzbekistan, Karakol sheep, the main goal of the development of the sheep breeding industry by the Soviet state, breeding sheep in the Kumkurgan region information about the importance of the factory, the organization of the AllUnion Agricultural Exhibition, the international fur auction, the increase in labor productivity of breeding sheep, the price of sheep products in Uzbekistan, the effect on sheep productivity, and the progress of the lambing seasons were analyzed
Keywords: Surkhondarya region; livestock; fodder